Revision of the genus Platygerris White, 1883 (Hemiptera: Heteroptera: Gerridae), with descriptions of two new species from Colombia - Burguez Floriano, Carla Fernanda [UNESP]; Molano-Rendon, Fredy; Morales, Irina; Figueiredo Moreira, Felipe Ferraz; Bispo, Pitagoras da Conceicao [UNESP] (Brill, 2020)
Platygerris White comprises true bugs that inhabit the surface of water in moderate to fast-flowing freshwater habitats. This genus differs from Cylindrostethus Mayr and Potamobates Champion (Gerridae: Cylindrostethinae) by having a short and flattened body; the mandibular and maxillary plates fused; and the omphalium, lateral groove, and lateral evaporatorium of the scent apparatus inconspicuous. In this paper, we redescribe Platygerris, describe two new species from Colombia, and redescribe P. asymmetricus Hungerford, P. caeruleus Champion and P. depressus White. In addition, we present an updated identification key to the species of the genus. For the first time, the cuticular structure is described for the genus based on electron microscopy.
Keywords: Neotropical Region; taxonomy; water striders